CTA Project Completion Report: Capitalizing on experiences for greater impact in rural development - Chavez-Tafur, Jorge (Technical Centre for Agricultural and Rural Cooperation, 2020)
The “Capitalizing on experiences for greater impact in rural development” project was a large-grant project which followed the proposal submitted to the International Fund for Agricultural Development (IFAD) and the agreement signed between the Technical Centre for Agricultural and Rural Cooperation and IFAD in March 2016. It was implemented by CTA and its partner organisations: the Food and Agriculture Organization of the United Nations (FAO) and the Inter-American Institute for Cooperation in Agriculture (IICA). The project lasted for 3 years, and involved projects and organisations working in different parts of the world. Following the structure and the list of activities outlined in the project proposal, during these 3 years the project • helped complete the FAO/IMARK learning module on experience capitalisation and supported the production of the Spanish and French versions; • built and maintained a thematic website, and completed it with an online repository with guidebooks and manuals as well as with the results of different capitalisation processes; • prepared, used and shared a series of training materials, together with a facilitators’ guidebook – building on the resources already available, but more specifically on the experience accumulated by the project; • ran a series of training workshops and supported the completion of experience-capitalisation processes in East Africa, Mozambique, India, West Africa (in French and in English), South East Asia, the Pacific region and Latin America; • completed the editing, layout and publication of 10 booklets with the results of the capitalisation processes started in different parts of the world (with more than 120 cases in total), together with two additional booklets focusing on the capitalisation process itself and on its institutionalization; • worked together with other organisations, such Farm Radio International and the International Land Coalition, in the analysis and documentation of their projects’ activities; • ran a series of webinars for online facilitators, focusing on the organisation and facilitation of a community of practice, and invited different participants to guide and facilitate the regional communities - in English (East and West Africa and in the Pacific region), French (West Africa), Portuguese (Brazil and Mozambique) and Spanish (Latin America); • presented the results achieved in international conferences and seminars (in Benin, Mauritania and the Netherlands); and • helped prepare a series of capitalisation processes within CTA, as part of a thorough analysis of its different intervention areas.